A new approach in linguistics - Khassenov, B.R.; Аdilova, A.S.; Тuite, E.E.; Ibrayeva, A.G. (KU Publ., 2022)
This article describes a new approach in modern Kazakh linguistics. The new approach is called ‘the mytholinguistic interpretation of the symbol point inside the circle (the point in the center of the circle)’. Using this approach, the authors try to answer the religious and philosophical question “where does the word begin?”. To find an answer to this difficult question, the article widely uses the results of research on speech ontogenesis, metaphysics, psychoanalysis, and materials from the Automated Similarity Judgment Program (ASJP) database, Austronesian Basic Vocabulary Database, S. Starostin’s etymological database (LWED) “Babel Tower” and dictionaries of Turkic languages (“An Etymological Dictionaries of Turkic Languages”, M. Kashgari’s Dictionary, “An Ancient Turkic Dictionary”). The information and conclusions presented in the study are of great interest not only to domestic scientists, but also to foreign researchers.
Лингвистикадағы жаңа тәсіл
Новый подход в лингвистике
Keywords: new approach; mytholinguistics; point inside the circle; ASJP; Austronesian Basic Vocabulary Database; children’s speech